Accuracy and validity of common dental terms using chat GPT model: a cross-sectional study - V., Keerthana Sree; Balasubramanian, Kumara Raja; Parangimalai Diwakar, Madan Kumar; Vasudevan, Menaka Sathish (International Journal Of Community Medicine And Public Health, 2024)
Background: Chat generative pre-trained transformer, an artificial intelligence chatbot can generate text-based content for information purpose. This study aims to find the accuracy and reliability of the chat GPT generated definitions for 30 common dental terms. Methods: A 15 current dental teaching staffs grading from Professors and Readers of various specialities participated in this study. They graded the chat GPT generated terms on a 5-point Likert scale (1- Strongly disagree, 2- Disagree, 3- Neutral, 4- Agree, 5- Strongly disagree). Scores were obtained and descriptive statistics was done and compared using Mann-Whitney U test. Results: Among 30 dental terms, 13 terms which were generated from the chat GPT model were found to be more appropriate when compared to text book definition. On comparison of reviewers’ perceptions for accuracy of definitions generated from chat GPT compared with text book definitions in which among the 30 dental terms, 9 terms were found to be statistically significant (p<0.05*). Conclusions: Chat GPT is a potential tool for answering knowledge based questions with equal vigor in the field of dentistry. Moreover, the accuracy of Chat GPT to solve questions in dentistry has a relational level of accuracy.